Implementasi Pengabdian Masyarakat melalui Pemberian Waktu Belajar Tambahan (LES) di SMP Negeri 2 Kartasura - Andrian Iswanto (CV. Multi Kreasi Media, 2023)
Since the spread of Covid-19 in Indonesia decreased in early 2022, the transition from online learning and limited face-to-face in schools began to gradually return to full face-to-face. SMP Negeri 2 Kartasura is one of the schools that implemented the policy. However, the problem is the decline in student enthusiasm and motivation in participating in learning and the material that has been taught during online learning has not been understood by students. Through the